Investigating the Phytotoxic Impacts of Next-Generation Lithiated Cobalt Oxide Nanomaterials - (:unkn) unknown (My University, 2023)
Lithium cobalt oxide nanosheets (LCO) are a type of next-generation transition metal oxide (TMO) nanomaterial and are one of the most commonly used cathode materials utilized in Li-ion batteries (LIB’s). With rapidly growing popularity of LIB’s as an energy storage technology, many consumer electronics and high-end electric vehicles have begun to incorporate these LIB’s into their design. And thus, the manufacturing rate of this nanomaterial has also skyrocketed to levels of environmental significance. However, despite its high levels of production, there is still little means for proper disposal of this nanomaterial, thus resulting in a highly probable environmental release. As LCO is a newer emerging contaminant of concern, we have only begun to study its potential environmental impacts. Recent studies have identified LCO as causing toxicity to eukaryotic organisms like Daphnia magna, Chironomus riparius, and Oncorhynchus mykiss, spanning a few trophic levels. However, there has yet to be any studies addressing the potential toxicity experienced by plant-type organisms. Thus, there is a major gap in our knowledge as to how LCO may impact ecological systems at the primary producing level, which is crucial for the proper structure and function of ecosystems. Additionally, we also have no data to suggest how environmental processes like photosynthesis will be impacted.This thesis addresses the phytotoxic impacts of LCO to Raphidocelis subcapitata, a freshwater microalga and model organism for environmental toxicology. In this work, different endpoints associated with physiological fitness, cellular phenotypes, and molecular interactions are investigated. Additionally, in order to predict the mechanism of action (MoA) through which LCO perturbs R. subcapitata, novel high-throughput phenotypic profiling (HTPP) methods were developed specifically for algal cells that employ multiplexed fluorescence cytochemistry coupled with high-content imaging (HCI). These HTPP methods were used to compare changes in the complex phenotypes of LCO-treated cells to that of compounds with known MoAs as a means to predict the phytotoxic MoA of LCO. The results of these investigations demonstrate impaired growth and net carbon biomass assimilation as physiological consequences of LCO exposure, while triggering an increase in chlorophyll and neutral lipid content. Furthermore, enhanced darkfield hyperspectral imaging revealed deposits of internalized LCO nanoparticles, thus suggesting the potential for LCO to directly interact with key subcellular components of R. subcapitata, as opposed to simply adhering to/covering the surface of the cells. Lastly, HTPP analyses revealed electron transport inhibition as the major phytotoxic MoA of LCO and demonstrated the irreversible oxidation of photosystem II (PSII) proteins, which are responsible for catalyzing the initial reaction of photosynthesis. Overall, these findings expand the mechanistic knowledge of LCO toxicity to plant-type organisms and the methods described in this work provide a novel framework for investigating chemical interactions within phycological entities.
Keywords: Algae; Aquatic Toxicology; Nanomaterials; Nanotoxicology; Phytotoxicity